2021
DOI: 10.3390/antiox10081273
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin Inhibits Autophagic Cell Death Induced by Bisphenol A in Human Dermal Fibroblasts

Abstract: Astaxanthin, a natural antioxidant carotenoid, is a nutrient with diverse health benefits, given that it decreases the risk of oxidative stress-related diseases. In the present study, we investigate the functional role of astaxanthin during autophagic cell death induced by the estrogenic endocrine-disrupting chemical bisphenol A (BPA) in normal human dermal fibroblasts (NHDF). BPA significantly induced apoptotic cell death and autophagy in NHDF. Autophagic cell death evoked by BPA was significantly restored up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…This can be attributed to its preventive role against the MMP expression in fibroblasts and its supportive action toward the expression of different biomarkers playing a role in wound healing [e.g., basic fibroblast growth factor (bFGF)] . Additionally, ASX can scavenge excessive intracellular reactive oxygen species (ROS) and reduce oxidative stress, thereby preventing dermal cellular damage by blocking apoptotic and autophagic pathways . On the other hand, in fibroblasts, ROS are known as signaling molecules that can trigger particular cell functions including cell differentiation, proliferation, death, and senescence and release of cytokines .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This can be attributed to its preventive role against the MMP expression in fibroblasts and its supportive action toward the expression of different biomarkers playing a role in wound healing [e.g., basic fibroblast growth factor (bFGF)] . Additionally, ASX can scavenge excessive intracellular reactive oxygen species (ROS) and reduce oxidative stress, thereby preventing dermal cellular damage by blocking apoptotic and autophagic pathways . On the other hand, in fibroblasts, ROS are known as signaling molecules that can trigger particular cell functions including cell differentiation, proliferation, death, and senescence and release of cytokines .…”
Section: Resultsmentioning
confidence: 99%
“…48 Additionally, ASX can scavenge excessive intracellular reactive oxygen species (ROS) and reduce oxidative stress, thereby preventing dermal cellular damage by blocking apoptotic and autophagic pathways. 49 On the other hand, in fibroblasts, ROS are known as signaling molecules that can trigger particular cell functions including cell differentiation, proliferation, death, and senescence and release of cytokines. 50 Therefore, fibroblast proliferation is assumed to be properly regulated by the presence of ASX.…”
Section: Cell Viability Of Ada-gel/bbg Constructsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Chalyk et al (2017) [52] observed that the levels of malondialdehyde (MDA), a recognised indicator of systemic oxidative stress, were reduced after a human model received 4 mg daily doses of astaxanthin (by 11.2% on day 15 and by 21.7% on day 29). Furthermore, Seong-Ryeong et al, (2021) [54] revealed astaxanthin as a nutritional supplement that prevents the skin fibroblastic autophagic cell death generated by bisphenol A (BPA) in normal human dermal fibroblasts (NHDF), as well as reduced the phosphorylation of extracellular signal-regulated kinases (ERK) driven by ROS generation. In NHDF, BPA dramatically increased apoptotic cell death and autophagy.…”
Section: Anti-ageingmentioning
confidence: 99%
“…This modulation includes reduction in the activities of the nuclear factor-κB (NF-κB) transcription system, activator protein 1 (AP-1), and mitogen-activated protein kinase (MAPK) [ 17 , 18 ], and improving the antioxidant defense mechanism [ 19 ]. Several studies, including our own, suggest that modulation of these signaling pathways by phytonutrients can lead to a reduction in inflammatory processes [ 20 , 21 , 22 ] and MMP expression [ 17 , 23 ], and increase collagen synthesis [ 17 ].…”
Section: Introductionmentioning
confidence: 99%